Exploring the psychological problems of mothers having the experience of death of children with untreatable genetic disorders: A qualitative study - Marzyeh Kermanian; Mahsa Khodayarian; Abbasali Dehghan Tafti; Naiire Salmani (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: A newborn with an untreatable genetic disorder could disrupt a family and affect parents' mental health, psycho-social interaction, and parent-child relationships. This study was conducted to explore the psychological problems of mothers having the children with untreatable genetic disorders. MATERIALS AND METHODS: This qualitative study was performed using the conventional content analysis method on 15 mothers having the children with untreatable genetic disorders selected by purposeful sampling. In-depth and semi-structured interviews were used to collect data. The recorded interviews were transcribed verbatim immediately and imported into MAXQDA10 software. Lundman and Granheim's content analysis method and Guba and Lincoln's proposed criteria for assessing rigor of the results were used. RESULTS: Overall, 1067 primary codes were extracted from the interviews and after the integration of similarities grouped into 19 sub-categories and three major categories including psychological reactions before diagnosis, after determined diagnosis, and after the child's death. CONCLUSIONS: The results showed that having the child with untreatable genetic disorder is considered as a notable psychological trauma and causes painful psychological reactions in parents. In this regard, the following approaches are recommended to health professionals: continuous monitoring of mental health of these families, developing a family education program, emotional and psychological support, and genetic counseling.